Health-seeking behaviors of pregnant women with hypertensive disorders of pregnancy in low- and middle-income countries: A scoping review protocol - Mariam Adam Al-Hassan; Jodie Bigalky; Solina Richter (PLOS One, 2026)
Hypertensive disorders of pregnancy (HDP) are among the leading causes of maternal and perinatal illness and death worldwide. Despite advances in its management, the burden of HDP remains disproportionately high in Low- and Middle-Income Countries (LMICs), where issues related to healthcare access, cultural beliefs, and systemic inefficiencies hinder timely diagnosis and intervention. Health-seeking behavior is crucial for preventing severe complications linked to HDP. An initial review of the literature was conducted and revealed no scoping or systematic reviews on the health-seeking behaviors of pregnant women with HDP in LMICs. We outline a scoping review protocol, using the JBI methodology, to map and synthesize existing evidence on the barriers and facilitators that influence the health-seeking behaviours of pregnant women with HDP in LMICs. The protocol is registered with the Open Science Framework ( https://doi.org/10.17605/OSF.IO/FTSR5 ). The data search and screening were completed on May 29 and June 28, 2025, respectively. Data extraction is ongoing. Study results and analysis are expected by December 2025, with journal submission and publication planned for January 2026. Findings will be valuable in providing a comprehensive overview of the current landscape of health-seeking behaviours, identifying gaps, and guiding appropriate care outcomes across settings in LMICs.